ANTIOXIDANT POTENTIAL OF RED AND WHITE CABBAGE: A COMPARISON - Huyen-Trang Thi Tran; Khairiza Lubis; Hau Van Doan; Thach N Ho; Kieu-Tien T Nguyen (JBIO: jurnal biosains (the journal of biosciences), 2022)
This study aimed to compare the antioxidant activity of white cabbage (B. oleracea var. capita f. alba) and red cabbage (B. oleracea var. capita f. rubra) in vitro. Dried cabbages were extracted by Soxhlet extraction using chloroform as solvent. The extracts were screened for phytochemicals followed by the antioxidant capacity measurement through free radical scavenging activity (DPPH and ABTS). The results showed that red cabbage extract (RCE) significantly had stronger antioxidant activity than white cabbage (WCE) (P<0,05). The IC50 values of RCE were 350,80 ± 5,27 µg/ml (DPPH) and 87,03 ± 1,92 µg/ml (ABTS) while these of WCE were 613,75 ± 8,76 µg/ml and 114,57± 0,41 µg/ml, respectively. Moreover, a higher level of phytoconstituents was found in RCE based on thin-layer chromatography analysis. These findings support that red cabbage has higher antioxidant activity than white cabbage which may be correlated with its phytoconstituents concentration.